2004
DOI: 10.1149/1.1646144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Novel Pad Groove Designs on Removal Rate and Uniformity of Dielectric and Copper CMP

Abstract: The effect of pad surface texture on dielectric and copper removal rates was studied theoretically and experimentally by investigating the fluid behavior of the slurry layer using methodologies similar to those found in tribological investigations of fluid bearings. It is shown that new nonfoamed hard plastic pads with intricate groove patterns are critical in modulating removal rates. Removal rate results of dielectric chemical mechanical polishing were in close agreement with model predictions for several of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
(3 reference statements)
0
19
0
Order By: Relevance
“…The grooves or perforations on the polishing pads have a significant impact on the polishing mechanism and outcome [15,16]. Grooves or perforations on the pad allow an effective slurry flow under the wafer surface and thus are very crucial for an effective CMP process.…”
Section: Polishing Pad Characteristicsmentioning
confidence: 99%
“…The grooves or perforations on the polishing pads have a significant impact on the polishing mechanism and outcome [15,16]. Grooves or perforations on the pad allow an effective slurry flow under the wafer surface and thus are very crucial for an effective CMP process.…”
Section: Polishing Pad Characteristicsmentioning
confidence: 99%
“…It has also been shown that (1) mostly applies to hard-pad CMP systems while RR is proportional to P 1.5 instead of P for soft-pad CMP systems [22]. More complete and accurate CMP models can be found in the literature [23][24][25][26][27][28][29]. CMP of polymer materials such as BCB polymers is more challenging than inorganic materials such as silicon dioxide and metals.…”
Section: Planarization Of Bcb Polymersmentioning
confidence: 99%
“…All of these features affect surface fluid transport. [5][6][7][8][9][10] • Pad and wafer both co-rotate during the entire process (either clockwise, or counter-clockwise). This causes advective transport in the radial direction along with centrifugal forces that grow stronger near the edge of the pad.…”
mentioning
confidence: 99%